Keabsahan Akta Yang Dibuat Oleh Calon Notaris Yang Sedang Magang Di Kantor Notaris - Milinia Mutiara Yusshinta Dewi; Bayu Indra Permana (Jurnal Ilmu Kenotariatan, 2022)
Notary is a public official who has the authority to make authentic deeds, who is appointed and dismissed by the government, namely by the Minister of Law and Human Rights and the Notary at the time of appointment by the Minister was not holding another position. Notaries in carrying out their state duties make a deed, namely in the form of a minuta deed (original deed). UUJN not only regulates the duties of a Notary, but also regulates authority, obligations and other matters within the scope of notary law. The law does not only regulate notaries but also regulates prospective notaries who are currently apprenticing at a notary's office. This research uses legal research methodology, normative juridical which uses statutory approaches, conceptual approaches, and historical approaches. The result of this study is from the provisions in Article 15 paragraph (1) of the UUJN it is explained that a Notary has the authority to make authentic deeds, in this case causing problems with the provisions of Article 16A paragraph (2) of the UUJN that a notary candidate who is currently an apprentice at a notary's office and has the obligation to keep confidential matters matters in the process of making the deed he made. The discrepancy between these articles causes problems in the form of unclear norms regarding the meaning of the deed drawn up by a notary candidate who is currently an apprentice at the notary apprentice's office in Article 16A paragraph (2) of the Law on the position of notary public. KEYWORDS: Authentic Deed, Prospective Notary, Apprenticeship, Notary.